Interdisciplinarity in teacher training in a LEDOC: challenges of teaching and learning - Maria Zenaide Alves; Wender Faleiro (Universidade Federal do Norte do Tocantins, 2019)
This text seeks to contribute to the debate about current challenges on interdisciplinary educational work, presenting a reflexive analysis of some practices developed within an interdisciplinary initial teacher education program. We start from the idea that in the Brazilian education exists a monoculture of knowledge which favors a fragmented and decontextualized way of organizing knowledge itself. This way of framing knowledge represents an obstacle to educators who have tried to adopt other pedagogies in all education levels. Therefore, we are confronted with the challenge of changing the Cartesian logic of the educative process, and a primary question that comes to our minds is: how can we put this change into practice? There is no single answer, nor a recipe for responding to this question. It is the scenario put before us who are professors of interdisciplinary undergraduate programs. Thus, this article shows some of the elements through which we have developed an interdisciplinary perspective. It is an approach that goes beyond the walls of the university and classroom boundaries. Starting from a reflection about contemporary teacher education, we also present some considerations regarding initial teacher training within the Degree in Rural Education. Finally, this piece discusses five practices developed in an interdisciplinary program focused on interdisciplinary teacher training at a Higher Education institution in Goias state.